A Student-Centric Analysis of Faculty Competences and Competencies for Effective Educational Experiences - Lozada, Paolo Roberto (JPAIR Multidisciplinary Research, 2024)
Competences represents different characteristics of a holistic approach to personal development and community engagement and Competencies are aspects that plays a crucial role in effective teaching and contributes to creating meaningful learning experiences for students. The objectives of the study are to determine the competences and competencies that provides effective teaching at San Sebastian College – Recoletos de Cavite Inc., to analyze the faculty performance based on student perspectives using the Student Evaluation of Teachers tool, and to develop recommendations for improving faculty competences and competencies from a student-centric perspective. The study used a descriptive quantitative design and evaluation results from the Center of Research and Creative Works of San Sebastian College – Recoletos de Cavite, Inc. are gathered to analyze the data. The evaluation of faculty competencies across three academic years (2020-2021, 2021-2022, and 2022-2023) reveals consistent high performance. In 2020-2021, the majority of faculty received high-level ratings in both competences and competencies, with 146 and 148 faculty members respectively. This trend continued in 2021-2022, with a significant increase to 352 and 356 faculty members receiving high-level ratings. The 2022-2023 data shows a slight decrease, with 183 and 186 faculty members rated at a high level. Across all years, very few faculty members were rated at low or very low levels, indicating overall strong faculty performance. Continuous curriculum adaptation, incorporating online teaching methods, and improving collaboration with the industry while supporting effective work-life routines will help educational institutions to improve their academic performance.